Modulação da atividade das interleucinas 17B e 25 associadas à melatonina como indutores de apoptose em cultivo celular de neoplasias mamárias - Gelaleti, Gabriela Bottaro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The development of mammary carcinogenesis involves neovascularization, deregulation of differentiation and apoptosis in tumor cells and the microenvironment. It is established that such effects may be controlled by melatonin, a hormone produced by the pineal gland that has oncostatic action on tumor cells and modulates interleukins (ILs) expression. IL-25, also known as IL-17E, is an active cytokine in inflammatory processes, capable of inducing apoptosis in tumor cells because of differential expression of its receptor (IL- 17RB). It is known that IL-17B competes with IL-25 for binding to receptor IL- 17RB on tumor cells, promoting tumorigenesis. The aim of this study was to investigate the action of melatonin and IL-25/IL-17B signaling in apoptosis and angiogenesis in breast tumor cells. Metastatic (MDA-MB-231 and CF-41), nonmetastatic (MCF-7 and CMT-U229) human and canine mammary tumor cell lines and human non-tumorigenic mammary epithelial cells (MCF-10A) were cultured in monolayer and three-dimensional structures on extracellular matrix rich in laminin (ECM) and treated for 48 hours with melatonin, IL-25, siIL-17B and the three combination therapies. Cell viability was measured by MTT assay, gene and protein expression by qRT-PCR and immunofluorescence, respectively. Also, a quantitative analysis of proteins present in the apoptotic pathway was performed after treatment with melatonin in the MDA-MB-231 and CF-41 cells. The treatment with 1 mM melatonin and 1 ng/mL of IL-25 significantly reduced the viability of human tumor cell lines (p < 0.05) and did not alter the cell viability of MCF-10A cells (p > 0.05). In canine cell lines, only 1 mM melatonin significantly reduced cell viability (p < 0.05). All three independent and combined treatments were able to significantly increase the protein expression of cleaved caspase-3 in all the tumor cells in monolayer and 3D structures (p < 0.05), which confirms the pro-apoptotic potential of ...

O desenvolvimento da carcinogênese mamária envolve a neovascularização, desregulação da diferenciação e apoptose nas células neoplásicas e no microambiente que estão inseridas. Está estabelecido que tais efeitos podem ser controlados pela melatonina, um hormônio produzido pela glândula pineal, que tem ação oncostática em células tumorais e modula a expressão de interleucinas (ILs). A IL-25, também conhecida como IL-17E, é uma citocina ativa em processos inflamatórios, capaz de induzir a apoptose em células tumorais devido à expressão diferencial do seu receptor (IL-17RB). Sabe-se que a IL-17B compete com a IL-25 pela ligação ao receptor IL-17RB em células tumorais, promovendo a tumorigênese. O objetivo deste estudo foi verificar a ação da melatonina e da sinalização IL-25/IL-17B no processo de apoptose e angiogênese em células tumorais mamárias. Linhagens tumorais mamárias humanas, metastática (MDA-MB-231) e não-metastática (MCF-7) e caninas, metastática (CF-41) e não-metastática (CMT-U229), e a linhagem epitelial mamária humana não tumorigênica (MCF-10A) foram cultivadas em monocamada e em estruturas tridimensionais em matriz extracelular ricas em laminina e tratadas por 48 horas com melatonina, IL-25, siIL-17B e os três tratamentos combinados. A viabilidade celular foi mensurada pelo ensaio de MTT, a expressão gênica e proteica por qRT-PCR e imunofluorescência, respectivamente. Além disso, uma análise quantitativa de proteínas presentes na via apoptótica foi realizada após o tratamento com melatonina nas células MDA-MB-231 e CF-41. Os tratamentos com 1 mM de melatonina e 1 ng/mL de IL-25 reduziram significativamente a viabilidade das linhagens tumorais humanas (p < 0,05) e não alteraram a viabilidade celular da linhagem MCF-10A (p > 0,05). Nas linhagens caninas, apenas 1 mM de melatonina reduziu significativamente a viabilidade celular (p < 0,05). Todos os três tratamentos independentes...
Keywords: Genética; Cancer - Aspectos geneticos; Mamas - Cancer; Interleucina-17; Melatonina; Apoptose; Neovascularização; Genetics